MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK KELOMPOK A MELALUI PERMAINAN SUSUN BALOK BERTEKSTUR DI PAUD AL-FIRDAUS KARENG KIDUL WONOMERTO PROBOLINGGO - Robiatul Adawiyah; Windasari, Indriana Warih (Al-ATHFAL: Jurnal Pendidikan Anak, 2023)
This research indicates that the consistent application of textured block games has a positive impact on enhancing the fine motor skills of children in the PAUD AL-FIRDAUS Kareng Kidul Wonomerto Probolinggo group. Utilizing the Classroom Action Research (PTK) method with 22 subjects aged 4-5 years, the study reveals a significant improvement in fine motor skills with the implementation of textured block games. In the pre-cycle, 28% of the 22 children showed improvement. In cycle I, the first meeting, 50% of the 22 children demonstrated an increase in fine motor skills, and in cycle II, the second meeting, 80.2% of the 22 children exhibited even higher improvement. The research concludes that playing with textured blocks is effective in enhancing children's fine motor skills, making it a potential model for improving fine motor skills in young children. The implications of this research can guide educators in PAUD to design learning activities that stimulate and enhance children's fine motor skills. Keywords: textured block play, fine motor skills